Different ways to organize the processes of financial administration : a field study of medium-sized Finnish companies - Nummela, Maria (2011)
This research concentrates on exploring the ways how financial administration is currently organized in medium-sized companies in Finland. Decentralization, centralization and outsourcing are options that are available to different-sized companies. The study was executed as a field study in seven medium-sized Finnish companies that represent different branches. Furthermore, the research method was qualitative theme interview. As large companies have already established their financial service centers and small enterprises have outsourced their financial administration to bookkeeping agencies, medium-sized companies are located between the two, finding a way that is suitable for their strategies. In addition, processes are important factors that reflect the state of the companies’ financial administration. That is why the study contains a closer review of certain processes: purchase-to-pay and order-to-cash in. The conclusion of the study was that these medium-sized companies have organized their financial administration rather similarly, nationally centralized and abroad decentralized. The systems and the processes are not harmonized but the companies rely on their staff, even though redundancies and rationalization have narrowed their operation fields. A few of the processes were already outsourced in some of the companies but overall opinions towards outsourcing were careful and deliberate.